Evaluation of effects of rehabilitation on trace elements and antioxidant status of patients with non-small cell lung cancer - Barinow-Wojewódzki, Aleksander; Mielcarz, Grzegorz (Contemporary Oncology/Współczesna Onkologia, 2008)
Aim of the study: The aim of this study was to explore the necessity and usefulness of the concept of rehabilitation as a team activity for patients with non-small lung cancer and to assess the relationship of increased chemoprevention of the organism measured as total body antioxidant status and changes in plasma essential microelements copper, zinc and selenium. Material and methods: Seventy men of age range 63±8 years who had already finished a radiotherapy programme were divided into three groups depending on physical efficiency. The first group had kinesitherapy, training and walking test; the second group had kinesitherapy and walking test; and the third group had walking test only (used as a control group). Plasma total antioxidant status (TAS) was measured by the FRAP (ferric reducing ability of plasma) method and copper, zinc and selenium determination was performed using flameless atomic absorption spectroscopy (Perkin-Elmer Zeeman 3030). Conclusions: We found a positive effect of kinesitherapy on chemopreventive system of the body. In the first and second group of patients, kinesitherapy had a positive effect on significant increases of TAS (p<0.01 and p<0.001 respectively) and selenium status in both groups (p<0.01), and plasma copper decreased only in the second group (p<0.05).